Implementation of Artificial Intelligence in Tahfidz Al-Qur'an Learning at Madrasah Tsanawiyah: A Study on the Effectiveness of Machine Learning-Based Applications - Tsaaniyatush Shoolihah Fauzan (Aslim: Journal of Education and Islamic Studies, 2025)
This study examines the implementation of machine learning-based Artificial Intelligence (AI) technology in enhancing the effectiveness of tahfidz Al-Qur'an learning at Madrasah Tsanawiyah (Islamic Junior High School). Using a quasi-experimental method with 120 students across three Madrasah Tsanawiyah institutions in Yogyakarta, this research compares the effectiveness of tahfidz learning using AI applications versus conventional methods. The developed application integrates speech recognition technology, natural language processing, and adaptive learning to provide real-time feedback on students' Qur'anic recitation. Research findings indicate significant improvements in memorization speed (p<0.05), tajwid accuracy (38% increase), and student learning motivation. This study provides empirical contributions to the integration of modern Islamic educational technology and opens opportunities for developing more effective and measurable tahfidz learning approaches.